2016
DOI: 10.1007/s11218-016-9343-0
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of adolescents’ emotional engagement in schoolwork

Abstract: This study explores the complexity of emotionally engaging schoolwork among students by analysing the interrelation between the affective and the social dimensions of emotional engagement. The data were collected from 78 Finnish sixth-grade (aged 12-13 years) and 89 eighth-grade (aged 14-15 years) students using picture tasks. The results show that the main elements of the affective dimension are the valuing of schoolwork and the enjoyment of learning, and the main element of the social dimension is a sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 58 publications
0
24
0
1
Order By: Relevance
“…There is a body of evidence showing that social support from teachers contributes to students' study engagement (Hughes et al 2008;Kiefer et al 2015;Košir and Tement 2014;Skinner et al 2008). For instance, a teacher-student relationship characterised by warmth and acceptance, or in other words, emotional support, is related to increased levels of study engagement, including the joy of learning and further academic success (Quin 2017;Roorda et al 2011;Ulmanen et al 2014Ulmanen et al , 2016bWu et al 2010). In addition, explicit information from teachers about the educational expectations and ways of effectively achieving these outcomes (i.e.…”
Section: Study Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a body of evidence showing that social support from teachers contributes to students' study engagement (Hughes et al 2008;Kiefer et al 2015;Košir and Tement 2014;Skinner et al 2008). For instance, a teacher-student relationship characterised by warmth and acceptance, or in other words, emotional support, is related to increased levels of study engagement, including the joy of learning and further academic success (Quin 2017;Roorda et al 2011;Ulmanen et al 2014Ulmanen et al , 2016bWu et al 2010). In addition, explicit information from teachers about the educational expectations and ways of effectively achieving these outcomes (i.e.…”
Section: Study Engagementmentioning
confidence: 99%
“…Kiefer et al 2015;Kindermann 2007;Skinner et al 2008;Wang and Eccles 2012). While numerous studies have reported a positive association between emotional support from peers and study engagement (Estell and Perdue 2013;Kiefer et al 2015;Urdan and Schoenfelder 2006;Wentzel et al 2017), other studies have found a negative relation between peer support and study engagement (Liu et al 2016;Ulmanen et al 2014Ulmanen et al , 2016b. The peer group's attitudes towards schoolwork have been suggested to mediate the relation between peer support and study engagement (Wang and Eccles 2012).…”
Section: Study Engagementmentioning
confidence: 99%
“…(Interview,Student 15) Thus, in school space social interactions influence students' concentration, and problems such as stress and headaches. Previous studies have also found that teachersupported promotion of interaction strengthens students' engagement (Patrick, Ryan, & Kaplan, 2007), and tensions with peers at school may hinder it (Ulmanen, Soini, Pietarinen, & Pyhältö, 2016). Most participating students also reported recurring absence from school, which complicates social interactions.…”
Section: Social Relations and Normsmentioning
confidence: 95%
“…This involves efforts to influence students´ sense of belonging and peer support (Lam et al, 2012;Oelsner, 2010). In any case, maintaining functional peer relations and engaging effectively in academic tasks seem to generate social tension among students (e.g., Furrer, 2010;Ulmanen, Soini, Pietarinen, & Pyhältö, 2016). Not only do functional teacher-student and peer relations appear to engage students effectively in academic tasks, but they also have the power to lessen school-related anxiety and cynicism (Denham et al, 2012;Hargreaves, 2000;Hart, 2014;King, 2015;Maslach & Jackson, 1981;Midgley & Edelin, 1998;Salmela-Aro et al, 2009;Stiglbauer et al, 2013).…”
Section: Emotional Engagement With Peersmentioning
confidence: 99%
“…The school-related anxiety (6 items, α = 0.67) and cynicism (5 items, α = 0.79) scales (Pietarinen et al, 2014) indicate negative affects in schoolrelated well-being. All the scales have been validated in prior studies (Ulmanen et al, 2016). The students rated all items on a five-point Likert scale (1 strongly disagree; 5 strongly agree).…”
Section: The Ecw Surveymentioning
confidence: 99%